Biocatalytic Foams from Microdroplet-Formulated Self-Assembling Enzymes - Hertel, Julian S (Advanced materials (Deerfield Beach, Fla.), 2023)
© 2023 The Authors. Advanced Materials published by Wiley-VCH GmbH.